DLC coating, its manufacturing method, equipment and composite coating, coating products

The DLC coating prepared by reacting silane monomers with hydrocarbon monomers prepared by the PECVD method solves the problems of insufficient color difference and bonding strength of the existing DLC ​​coating on the touch panel, and achieves high transparency, low color difference and high scratch resistance. It is suitable for high-demand touch panels and other products.

JP2025512104APending Publication Date: 2025-04-16JIANGSU FAVORED NANOTECHNOLOGY CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
JP2024560615
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2022-04-15
Filing Date
2023-03-15
Publication Date
2025-04-16

Smart Images

  • Figure 2025512104000001_ABST
    Figure 2025512104000001_ABST
Patent Text Reader

Abstract

In a specific embodiment of the present invention, there is provided a DLC coating, its manufacturing method, equipment, and composite coating and application product. The DLC coating is formed by depositing a hydrocarbon monomer and a silane monomer using a PECVD method, and can be reacted and deposited at room temperature to form a coating, effectively avoiding the impact of relatively high temperatures on substrate performance in conventional deposition methods. Furthermore, the DLC coating formed in a specific embodiment of the present invention has the properties of low color difference, high transparency and high bonding strength, and its manufacturing method is simple, which is conducive to process production. Furthermore, the composite coating obtained by depositing an AF coating on the DLC coating has the properties of low color difference, high transparency and further scratch resistance, and is particularly suitable for application products such as touch panels.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] This application claims priority from a Chinese patent application, application number 202210395178.5, filed with the China Patent Office on April 15, 2022, entitled "DLC coating, its manufacturing method, equipment and composite coating, and application product," the entire contents of which are incorporated herein by reference.

[0002] The present invention belongs to the field of chemical coatings, specifically to DLC coatings, their manufacturing methods, equipment and composite coatings, and applied products. [Background technology]

[0003] In recent years, with the continuous innovation of Internet technology and industrial manufacturing technology, people's daily life has entered the multimedia era, and touch screens and various innovative wearable electronic devices are seen everywhere in life and the workplace, bringing great interest and convenience to daily life and work. As touch control becomes more widespread, its inherent characteristics of being easily scratched and easily marked with fingerprints will affect the appearance, but will also affect the use of functions and bring about bad use experiences. Therefore, it is necessary to form a layer of AF (anti-fingerprint) coating on its surface, and Daikin Co., Ltd. has put forward a fluorinated pill deposition technology that has greatly improved the wear resistance and fingerprint resistance, and has been widely recognized in the industry. However, with the continuous increase in use needs and the update of application scenarios, the wear resistance requirements for smart touch panels are becoming higher and higher, so it is necessary to break through the original technical constraints.

[0004] DLC (diamond-like coating) coatings are formed by hybridization of carbon allotropes, combining the hardness and wear resistance of diamond with the flexibility and lubricity of graphite, giving DLC ​​coatings wide applicability. However, in touch panels (PC, glass, PMMA, etc.), the two main problems that limit the use of DLC coatings are the color difference of the film layer, which affects the light transmittance, and the other problem is the bonding strength of the film layer, which should be noted both in terms of the bonding with the substrate and the bonding strength of the subsequently deposited oleophobic layer. In recent years, researchers have improved the overall performance of the film layer by doping new elements into DLC coatings, and the main doped elements are Ti, Cr, Zr, Si, N, etc. For example, a diamond-like carbon coating with a low friction coefficient can be obtained by preparing silicon-doped DLC coatings by DC magnetron sputtering, mid-frequency magnetron sputtering, and ion-assisted deposition. On the one hand, this method requires the simultaneous combination of multiple discharge methods, which complicates the structure of the equipment and increases the manufacturing costs; on the other hand, the deposition temperature exceeds 150°C, which is higher than the maximum thermal deformation temperature of common touch panel materials, such as polymer materials such as PMMA and PC, and therefore cannot meet the industrially stable production needs of the touch panel field. Summary of the Invention [Problem to be solved by the invention]

[0005] A specific embodiment of the present invention provides a DLC coating with low color difference, high transparency and high bonding strength, which is manufactured by a PECVD (Plasma Enhanced Chemical Vapor Deposition) method, which is easy to manufacture and contributes to process production, and an anti-fingerprint composite coating with low color difference, high transparency and further scratch resistance manufactured thereby, and the specific aspects are as follows: [Means for solving the problem]

[0006] DLC coating, C x1 H y1 (x1 is an integer of 1 to 10, and y1 is an integer of 2 to 22), and x2 H y2 S z (x2 is an integer of 0 to 32, y2 is an integer of 4 to 68, and z is an integer of 1 to 4) is deposited by a PECVD method to form a DLC coating.

[0007] Preferably, the hydrocarbon monomer and the silane monomer have a boiling point of 100° C. or less at normal pressure.

[0008] Preferably, the hydrocarbon monomer is methane, acetylene, benzene, or ethylene.

[0009] Preferably, the silane monomer is silane, methylsilane, dimethylsilane, trimethylsilane, tetramethylsilane, ethylsilane, or diethylsilane.

[0010] Preferably, the molar ratio of the hydrocarbon monomer to the silane monomer is between 60:40 and 95:5.

[0011] Preferably, the DLC coating has a thickness of 5 to 100 nm.

[0012] The DLC coating manufacturing apparatus includes: a plasma reactor for depositing the DLC coating by PECVD; a monomer gasification control device for heating and gasifying a hydrocarbon monomer that is liquid at room temperature, or for controlling the state of gasification of a silane monomer; a gas flow meter for measuring a flow rate of the monomer whose gasification has been controlled; a heat-insulating device used to insulate a monomer flow path to ensure stable introduction of gasified monomer in the monomer gasification control device to the plasma reactor.

[0013] Preferably, the apparatus further includes a pressure gauge disposed between the monomer gasification controller and the gas flow meter, and controls the temperature of the monomer gasification controller based on a value read from the pressure gauge.

[0014] A method for producing the DLC coating, comprising the steps of: providing a substrate and placing the substrate in a plasma reactor; metering the hydrocarbon monomer and silane monomer gases into the plasma reactor and turning on a bias power supply to deposit a DLC coating on the substrate by a PECVD process.

[0015] Preferably, the hydrocarbon monomer and the silane monomer are each introduced as a gas and metered by a gas flow meter.

[0016] Preferably, the pressure of the silane monomer gas is controlled to 0.001 MPa to 0.003 MPa by controlling the temperature of the silane monomer.

[0017] Preferably, the flow rate of the hydrocarbon monomer is 10 to 200 sccm, and the flow rate of the silane monomer is 5 to 100 sccm.

[0018] Preferably, an inert gas is introduced at a flow rate of 20 to 200 sccm while the monomer gas is being introduced.

[0019] Preferably, the pressure in the plasma reactor is 15-100 mT, the bias voltage input is -200--800 V, and the deposition time of the coating is 2-30 min.

[0020] A composite coating comprising the above DLC coating and an AF coating formed on the DLC coating.

[0021] Preferably, the raw material of the AF coating comprises a perfluoropolyether polymer.

[0022] Preferably, the perfluoropolyether polymer is a perfluoropolyether silane or a perfluoropolyether alkoxy silane.

[0023] Preferably, the thickness of the AF coating is from 5 to 20 nm.

[0024] Preferably, the AF coating is deposited by vacuum evaporation.

[0025] An application product, at least a portion of the surface of which is provided with a composite coating as described above.

[0026] Preferably, the product is a touch panel.

[0027] Preferably, the coated product has a color difference value before and after coating of 0.5 or less.

[0028] Preferably, the substrate of the coating surface of the product is glass, and according to the steel wool test, after 6000 reciprocations under a load of 10N, the speed is 40 cycles / min, the test direction is the same as the fiber direction of the steel wool, the test stroke is 40mm, and the contact angle is observed to be more than 100°.

[0029] Preferably, the substrate of the coating surface of the product is plastic, and according to the steel wool test, after 800 reciprocations under a load of 1N, the speed is 40 cycles / min, the test direction is the same as the fiber direction of the steel wool, the test stroke is 40mm, and the contact angle is observed to be greater than 100°. Effect of the Invention

[0030] According to the DLC coating of a specific embodiment of the present invention, the DLC coating is deposited by a PECVD method from a hydrocarbon monomer and a silane monomer, and the coating can be formed by reacting and depositing at room temperature, effectively avoiding the influence of high temperature on the performance of the substrate in the conventional coating method. Moreover, the DLC coating formed in the specific embodiment of the present invention has the properties of low color difference, high transparency and high bonding strength, and its manufacturing method is simple and conducive to process production. Furthermore, the anti-fingerprint composite coating obtained by depositing an AF coating on the DLC coating has low color difference, high transparency and further scratch resistance, and is particularly suitable for application products such as touch panels. [Brief description of the drawings]

[0031] [Figure 1] FIG. 1 is a schematic diagram of a DLC coating manufacturing apparatus according to a specific embodiment of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0032] In a specific embodiment of the invention, the DLC coating is x1 H y1 (x1 is an integer of 1 to 10, and y1 is an integer of 2 to 22), and x2 H y2 S z (x2 is an integer of 0 to 32, y2 is an integer of 4 to 68, and z is an integer of 1 to 4), by a PECVD method to form a DLC coating.

[0033] In a specific embodiment of the DLC coating of the present invention, silicon is doped by PECVD and reacted and deposited at room temperature to form a coating, which effectively avoids the impact of high temperature on the performance of the substrate in conventional coating methods and is suitable for conventional polymer materials used in touch panels, such as PC and PMMA. Moreover, the innovative application of silicon doping technology to touch panels can solve the problem of DLC easily becoming yellowed or discolored.

[0034] Regarding the DLC coating of specific embodiments of the present invention, in some specific embodiments, the hydrocarbon monomer and silane monomer have a boiling point of 100°C or less at normal pressure. By using a monomer with a boiling point of 100°C or less, the state of gasification of the monomer can be easily controlled, and therefore the ratio of the hydrocarbon monomer and the silane monomer can be accurately and continuously controlled by better controlling the flow rate of the gas monomer, so that the ratios of carbon, hydrogen and silicon in the DLC can be accurately controlled, thereby better ensuring the hardness, low color difference and high transparency properties of the DLC coating.

[0035] For the DLC coating of specific embodiments of the present invention, in some specific embodiments, x1 is an integer of 1 to 4, y1 is an integer of 2 to 10, x2 is an integer of 0 to 16, y2 is an integer of 4 to 36, and z is 1.

[0036] For the DLC coatings of specific embodiments of the present invention, in some specific embodiments, the hydrocarbon monomer may be an alkyne, such as acetylene or propyne, an alkene, such as ethylene or acrylic, an alkane, such as methane, ethane, or propane, or an aromatic hydrocarbon, such as benzene, and the hydrocarbon monomer may be one or more.

[0037] For the DLC coating of the specific embodiment of the present invention, in some specific embodiments, the molar ratio of the hydrocarbon monomer to the silane monomer is in the range of 60:40 to 95:5, and specifically may be, for example, 60:40, 65:35, 70:30, 75:25, 80:20, 85:15, 90:10, or 95:5.

[0038] According to the DLC coating of the specific embodiment of the present invention, in some specific embodiments, the thickness of the DLC coating is 5 to 100 nm, and specifically may be, for example, 5 nm, 10 nm, 15 nm, 20 nm, 25 nm, 30 nm, 35 nm, 40 nm, 45 nm, 50 nm, 55 nm, 60 nm, 65 nm, 70 nm, 75 nm, 80 nm, 85 nm, 90 nm, 95 nm, or 100 nm.

[0039] A specific embodiment of the present invention further provides an apparatus for producing the above DLC coating, comprising: a plasma reactor for depositing the DLC coating by PECVD; a monomer gasification control device for heating and gasifying a hydrocarbon monomer that is liquid at room temperature, or for controlling the gasification state of a silane monomer; a gas flow meter for measuring a flow rate of the monomer whose gasification has been controlled; and a heat retention device used to keep a monomer flow path warm so as to ensure stable introduction of gasified monomer in the monomer gasification control device to the plasma reactor.

[0040] Hereinafter, the DLC coating manufacturing apparatus of a specific embodiment of the present invention will be described with reference to FIG. 1. As shown in FIG. 1, it is a schematic diagram of the DLC coating manufacturing apparatus of a specific embodiment of the present invention. a plasma reactor 1 for depositing by PECVD to form a DLC coating; a monomer gasification control device for heating and gasifying a hydrocarbon monomer that is liquid at room temperature, or for controlling the gasification state of a silane monomer; a first gas flow meter 6 for accurately measuring the monomer flow rate at which gasification is controlled; and a heat-insulating device for insulating a monomer flow path to ensure that the gasified monomer is in a gasified state during introduction into the plasma reactor 1.

[0041] Regarding the DLC coating manufacturing apparatus of the specific embodiment of the present invention, in some specific embodiments, the monomer gasification control device includes a monomer container 2 and a temperature control device 3, in some specific embodiments, the monomer in the monomer container 2 is a hydrocarbon monomer that is liquid at room temperature, and the monomer container 2 is heated by the temperature control device 3 to gasify the hydrocarbon monomer that is liquid at room temperature, so that the amount of the hydrocarbon monomer that is liquid at room temperature can be accurately measured by the first gas flow meter 6, in some specific embodiments, the monomer in the monomer container 2 is a silane monomer, and the monomer container 2 is kept at an appropriate temperature by the temperature control device 3, so that the amount of the silane monomer introduced can be accurately measured by the first gas flow meter 6, and in some specific embodiments, the temperature control device 3 is a water bath or oil bath device.

[0042] Regarding the DLC coating manufacturing apparatus of the specific embodiment of the present invention, in some specific embodiments, a pressure gauge 4 is provided between the monomer gasification control device and a first gas flow meter 6, and the temperature of the monomer gasification control device is controlled based on the value read from the pressure gauge, for example, in some specific embodiments, the temperature of the temperature control device 3 is adjusted by monitoring the pressure gauge 4, and the pressure is controlled to 0.001 MPa to 0.003 MPa.

[0043] Regarding the DLC coating manufacturing apparatus of the specific embodiment of the present invention, in some specific embodiments, the DLC coating manufacturing apparatus further includes a second gas flow meter 7 that accurately measures and controls the flow rate of a hydrocarbon monomer that is a gas at room temperature, such as methane, ethylene, or acetylene.

[0044] Regarding the DLC coating manufacturing apparatus of the specific embodiment of the present invention, in some specific embodiments, the hydrocarbon monomers and silane monomers that are liquid at room temperature are multiple, and the corresponding monomer gasification control devices and first gas flow meters 6 are correspondingly multiple.

[0045] For the DLC coating manufacturing apparatus of the specific embodiment of the present invention, in some specific embodiments, the number of hydrocarbon monomers that are gaseous at room temperature is multiple, and the number of the second gas flow meters 7 corresponding thereto is correspondingly multiple.

[0046] In some specific embodiments, the DLC coating manufacturing apparatus of the specific embodiment of the present invention further includes another second gas flow meter 7 for measuring and introducing an inert carrier gas, such as helium gas or argon gas.

[0047] As for the DLC coating manufacturing apparatus of the specific embodiment of the present invention, in some specific embodiments, it further includes a gas mixing device 5 for uniformly mixing multiple monomer gases before entering the plasma reactor 1.

[0048] In the DLC coating manufacturing apparatus of a specific embodiment of the present invention, the flow rate of the gasified monomer, especially the flow rate of the gasified monomer of silane, is controlled to precisely control the proportion of the monomer, thereby precisely controlling the proportions of carbon, hydrogen, and silicon in the DLC coating, thereby better ensuring the hardness, low color difference, and high transparency properties of the DLC coating.

[0049] In a specific embodiment of the present invention, the method for producing a DLC coating as described above further comprises the steps of: providing a substrate and placing the substrate in a plasma reactor; and metering the hydrocarbon monomer and silane monomer gases into the plasma reactor and turning on a bias power supply to deposit a DLC coating on the substrate by a PECVD process.

[0050] Regarding the method for producing the DLC coating of the specific embodiment of the present invention, in some specific embodiments, the material of the substrate is metal, ceramic, plastic, glass, etc.

[0051] Regarding the manufacturing method of the DLC coating of the specific embodiment of the present invention, in some specific embodiments, the substrate is a touch panel.

[0052] Regarding the manufacturing method of the DLC coating of the specific embodiment of the present invention, in some specific embodiments, the substrate is further subjected to a cleaning treatment in order to reinforce the bonding strength between the plasma coating and the substrate. For example, in some specific embodiments, before applying the DLC coating, 0-200 sccm of argon gas and / or 0-200 sccm of oxygen gas are introduced, the pressure is controlled to 15-100 mT, the bias power supply is turned on, a voltage of -300 to -1000 V is supplied, and the substrate is bombarded and cleaned for 5-20 min, and contaminants such as oxides on the surface of the product substrate are neatly etched, and an interface with high surface energy is formed, providing a good deposition foundation for DLC.

[0053] Regarding the manufacturing method of the DLC coating of the specific embodiment of the present invention, in some specific embodiments, for the hydrocarbon monomer which is gaseous at room temperature, the amount of the hydrocarbon monomer which is gaseous at room temperature is directly and accurately measured by a gas flow meter; for the hydrocarbon monomer which is liquid at room temperature, it is first heated to be gasified and the amount of the hydrocarbon monomer which is liquid at room temperature is accurately measured by a gas flow meter; for the silane monomer, its temperature is controlled and its pressure is controlled to be 0.001 MPa to 0.003 MPa, and the amount of the silane monomer which is introduced is further accurately measured by a gas flow meter, thereby accurately controlling the proportion of the monomer, and therefore accurately controlling the proportions of carbon, hydrogen and silicon in the DLC coating, thereby better ensuring the properties of hardness, low color difference and high transparency of the DLC coating.

[0054] Regarding the manufacturing method of the DLC coating of the specific embodiment of the present invention, in some specific embodiments, the flow rate of the hydrocarbon monomer is 10-200 sccm, the flow rate of the silane monomer is 5-100 sccm, and the molar ratio of the hydrocarbon monomer to the silane monomer is 60:40-95:5, specifically, for example, 60:40, 65:35, 70:30, 75:25, 80:20, 85:15, 90:10, or 95:5, etc., and the specific molar ratio of the hydrocarbon monomer to the silane monomer is adjusted and controlled according to the material of the substrate, the specific hydrocarbon monomer, the silane monomer, and actual needs.

[0055] Regarding the method for producing a DLC coating according to a specific embodiment of the present invention, in some specific embodiments, an inert gas, such as argon gas or neon gas, is introduced while introducing the monomer gas, and the flow rate of the inert gas is 20 to 200 sccm.

[0056] Regarding the manufacturing method of the DLC coating of the specific embodiment of the present invention, in some specific embodiments, the pressure in the plasma reactor is 15 to 100 mT, the bias voltage input is -200 to -800 V, and the deposition time of the coating is 2 to 30 min.

[0057] For the method of producing the DLC coating of the specific embodiment of the present invention, the explanation for the hydrocarbon monomer and the silane monomer is as above.

[0058] A specific embodiment of the present invention further provides a composite coating comprising a DLC coating as described above and an AF coating formed on said DLC coating.

[0059] Regarding the composite coating of a specific embodiment of the present invention, the DLC coating doped with Si element provides good connecting sites for the AF coating, so that even if the process of depositing silicon dioxide before applying the AF coating is canceled, excellent bonding strength between the AF and the touch panel can be obtained. In addition, the hardness of the DLC coating (up to 1500HV) is higher than that of silicon dioxide (up to 1100HV), which further improves the mechanical durability of the AF coating and significantly reinforces the wear resistance of the AF coating.

[0060] For the composite coating of the specific embodiment of the present invention, in some specific embodiments, the raw material of the AF coating is the raw material of a normal AF coating, for example, in some specific embodiments, the raw material of the AF coating is a fluorine-based material, such as a perfluoropolyether polymer or other suitable fluorine-based material. In some specific embodiments, the perfluoropolyether polymer is a perfluoropolyether silane or a perfluoropolyether alkoxysilane. Specifically, in some specific embodiments, the perfluoropolyether polymer may be UD509 manufactured by Daikin Industries, Ltd., KY-178, KY-185, KY-1900 manufactured by Shin-Etsu Chemical Co., Ltd., Fomblin manufactured by SOLVAY, etc.

[0061] Regarding the composite coating of the specific embodiment of the present invention, in some specific embodiments, the thickness of the AF coating is 5-20 nm, specifically, for example, 5 nm, 10 nm, 15 nm, or 20 nm, etc.

[0062] Regarding the composite coating of the specific embodiment of the present invention, in some specific embodiments, the AF coating is formed by vacuum deposition, and in some specific forms, the AF coating may be formed by other methods, such as spraying, electroplating, etc.

[0063] Particular embodiments of the present invention further provide an application product comprising, on at least a portion of a surface thereof, a composite coating as described above.

[0064] Regarding the application product of the specific embodiment of the present invention, in some specific embodiments, the product is a touch panel, such as a touch panel of a mobile phone, a tablet, a car display, a television, or an LED, and in some specific embodiments, the product is an electrical product, a building product, or any product that requires transparency, scratch resistance, or abrasion resistance.

[0065] For the application products of specific embodiments of the present invention, in some specific embodiments, the color difference value of the application product before and after application is 0.5 or less, in some specific embodiments, the color difference value of the application product before and after application is 0.4 or less, and in some specific embodiments, the color difference value of the application product before and after application is 0.3 or less.

[0066] The coating product of the specific embodiment of the present invention has excellent abrasion resistance. In some specific embodiments, the substrate of the coating surface of the product is glass. According to the steel wool test, it is observed that after 6000 reciprocations under a load of 10N, the speed is 40 cycles / min, the test direction is the same as the fiber direction of the steel wool, the test stroke is 40 mm, and the contact angle is 100° or more. In some specific embodiments, the substrate of the coating surface of the product is glass. According to the steel wool test, it is observed that after 7000 reciprocations under a load of 10N, the speed is 40 cycles / min, the test direction is the same as the fiber direction of the steel wool, the test stroke is 40 mm, and the contact angle is 100° or more. In some specific embodiments, the substrate of the coating surface of the product is glass. According to the steel wool test, it is observed that after 8000 reciprocations under a load of 10N, the speed is 40 cycles / min, the test direction is the same as the fiber direction of the steel wool, the test stroke is 40 mm, and the contact angle is 10 It has been observed that the contact angle is greater than or equal to 100° in some specific embodiments, the substrate of the coating surface of the product is plastic, and after 800 reciprocations under a load of 1N, the speed is 40 cycles / min, the test direction is the same as the fiber direction of the steel wool, the test stroke is 40mm, and the contact angle is greater than or equal to 100° in some specific embodiments, the substrate of the coating surface of the product is plastic, and after 900 reciprocations under a load of 1N, the speed is 40 cycles / min, the test direction is the same as the fiber direction of the steel wool, the test stroke is 40mm, and the contact angle is greater than or equal to 100° in some specific embodiments, the substrate of the coating surface of the product is plastic, and after 1000 reciprocations under a load of 1N, the speed is 40 cycles / min, the test direction is the same as the fiber direction of the steel wool, the test stroke is 40mm, and the contact angle is greater than or equal to 100° in some specific embodiments.

[0067] The present invention will now be further described with reference to specific examples.

[0068] Working Example Explanation of the test method Contact angle of coating: Tested according to GB / T 30447-2013 standard.

[0069] Coating light transmittance and color difference: Calculated according to GB11186.3-1989 standard, using Konica Minolta spectrophotometer CM-5 and selecting C light source for detection, the test result is ΔE indicates color difference,

number

[0070] Abrasion resistance test: using a Taber 5900 reciprocating abrasion tester and Bonstar #0000 steel wool, a load of 10 N was used for the glass substrate, and a load of 1 N was used for the plastic substrate, the speed was 40 cycles / min, the test direction was the same as the fiber direction of the steel wool, the test stroke was 40 mm, and the number of times the contact angle was less than 100° was observed.

[0071] Example 1 The surface of the glass touch panel was purged clean with dry nitrogen gas and placed into the vacuum cavity of the plasma reactor, and the impurity gas in the cavity was discharged through the vacuum pump unit, and when the vacuum pressure was less than 0.05mT, 100sccm of argon gas was introduced and the pressure was controlled at 30mT, and the bias power supply was turned on to supply a voltage of -400V, and the substrate was bombarded and cleaned for 5min. Then, the power supply and the gas source are turned off, the water bath is turned on to control the water bath temperature at 26°C, the pressure value of the tetramethylsilane monomer gas is controlled at 0.001MPa to 0.003MPa at this temperature, the gas flow valve is adjusted to control the flow rate of the tetramethylsilane monomer to 40sccm, the flow rate of the argon gas to 100sccm, and the flow rate of the methane to 80sccm, which are introduced into the gas mixer to be mixed, and then introduced into the plasma reactor, the pressure in the cavity of the plasma reactor is controlled at 30mT, the bias power supply is turned on, and a voltage of -300V is input, the coating time is 10min, and one layer of 20nm high transparency and high hardness DLC coating is deposited and obtained, after which the power supply, the gas source and the pump unit are turned off in sequence, and the cavity door of the plasma reactor is opened to take out the glass touch panel.

[0072] The glass touch panel with DLC coating was placed in the AF evaporation cavity and measured with a 3.0×10 -3 The vacuum was drawn to 1 Pa, and UD509AF liquid was introduced. During evaporation, the current was 12 A and the time was 800 s. One layer of 10 nm AF coating was evaporated, and then the glass touch panel was taken out.

[0073] The glass touch panel on which the DLC coating and the AF coating were deposited in this order was subjected to light transmittance, color difference, and abrasion resistance tests, and the results are shown in Table 1 below.

[0074] Example 2 The glass touch panel of Example 1 was changed to a PC touch panel, the 100 sccm argon gas introduced in the substrate cleaning step was changed to 100 sccm oxygen gas, the cleaning time was extended to 20 minutes, and other process steps were left unchanged. The PC touch panel on which the DLC coating and the AF coating were deposited in sequence was subjected to light transmittance, color difference, and abrasion resistance tests. The results are shown in Table 1 below.

[0075] Example 3 The glass touch panel in Example 1 was changed to a PMMA touch panel, the etching cleaning time was shortened to 2 minutes, and other process steps were left unchanged. The PMMA touch panel on which the DLC coating and the AF coating were deposited in sequence was subjected to light transmittance, color difference, and wear resistance tests. The results are shown in Table 1 below.

[0076] Example 4 The water bath temperature of Example 1 was set to 10°C, the tetramethylsilane monomer was replaced with trimethylsilane monomer, and the parameters of other process steps were kept the same. The glass touch panel on which the DLC coating and the AF coating were deposited in sequence was subjected to light transmittance, color difference and wear resistance tests, and the results are shown in Table 1 below.

[0077] Comparative Example 1 The surface of the glass touch panel was purged with dry nitrogen gas and placed in the vacuum cavity of the plasma reactor, and the impurity gas in the cavity was discharged through the vacuum pump unit, and when the vacuum pressure was less than 0.05mT, 100sccm of argon gas was introduced and the pressure was controlled at 30mT, and the bias power supply was turned on to supply a voltage of -400V, and the substrate was bombarded and cleaned for 5min, removed, and a 20nm silicon dioxide layer and a 10nm UD509AF layer were sprayed on the surface by normal spraying. The light transmittance, color difference, and wear resistance tests were conducted on the coated glass touch panel, and the results are shown in Table 1 below.

[0078] Comparative Example 2 The surface of the glass touch panel is cleaned and purged with dry nitrogen gas, then placed into the vacuum cavity of the plasma reactor, and the impurity gas in the cavity is exhausted through the vacuum pump unit, when the vacuum pressure is less than 0.05mT, 100sccm of argon gas is introduced, and the pressure is controlled at 30mT, and the bias power supply is turned on to supply a voltage of -400V, and the substrate is bombarded and cleaned for 5min, then taken out and placed into the evaporation cavity, first, 4.0×10 -3 The vacuum was drawn to a low pressure of 3.0×10 Pa or less, and the current of the deposition boat containing silicon dioxide was set to 30 A for 120 s to deposit one silicon dioxide layer of 20 nm. -3 The vacuum was drawn to 10 Pa, and the UD509AF solution was introduced into another deposition boat, and the current of the deposition boat was set to 12 A for 800 s to deposit one layer of 10 nm AF coating, and the glass touch panel was then taken out. The coated glass touch panel was subjected to light transmittance, color difference, and abrasion resistance tests, and the results are shown in Table 1 below.

[0079] Comparative Example 3 The flow rate of the tetramethylsilane monomer in Example 1 was set to zero, the coating time was extended to 15 min, and the parameters of other process steps were kept the same, and a 20 nm DLC coating was obtained by deposition, and then a 10 nm AF coating was manufactured under the same process conditions. The glass touch panel on which the DLC coating and the AF coating were sequentially deposited was subjected to light transmittance, color difference, and abrasion resistance tests, and the results are shown in Table 1 below.

[0080] Comparative Example 4 Glass touch panels that were only purged with dry nitrogen gas but had no coating were subjected to light transmission testing with the results shown in Table 1 below.

[0081] Comparative Example 5 PC touch panels that were only purged with dry nitrogen gas but had no coating were subjected to light transmittance testing with the results shown in Table 1 below.

[0082] Comparative Example 6 The PMMA touch panels that were only purged with dry nitrogen gas but had no coating were subjected to light transmission testing with the results shown in Table 1 below. TIFF2025512104000003.tif70124

[0083] From Table 1 above, it can be seen that the coated glass touch panels of Examples 1 and 4 and the uncoated glass touch panel of Comparative Example 4 have almost the same light transmittance, the coated PC touch panel of Example 2 and the uncoated PC touch panel of Comparative Example 5 have almost the same light transmittance, and the coated PMMA touch panel of Example 3 and the uncoated PMMA touch panel of Comparative Example 6 have almost the same light transmittance. This shows that the DLC coating and composite coating of the present invention have excellent light transmittance, and the durability of Example 1 is excellent. The abrasion resistance number is much higher than that of Comparative Example 1 and Comparative Example 2, which shows that the composite coating of the present invention has better scratch resistance compared to the composite coatings of Comparative Example 1 and Comparative Example 2. Compared with Example 1, the DLC coating of Comparative Example 3 is not doped with Si by introducing tetramethylsilane monomer, and its light transmittance is significantly reduced, color difference is significantly improved, and the abrasion resistance number is drastically reduced, which shows that the composite coating obtained by depositing an AF coating on the DLC coating described in the present invention has low color difference, high transparency, and better scratch resistance.

[0084] The present invention has been disclosed above, but is not limited thereto. Those skilled in the art may make various changes and modifications without departing from the spirit and scope of the present invention, and therefore, it should be understood that the scope of protection of the present invention should be based on the scope defined by the claims.

Claims

1. A DLC coating, x1 H y1 (wherein x1 is an integer of 1 to 10, and y1 is an integer of 2 to 22) and a hydrocarbon monomer represented by C x2 H y2 S z (x2 is an integer from 0 to 32, y2 is an integer from 4 to 68, and z is an integer from 1 to 4) and a silane monomer represented by the following formula (1):

2. 2. The DLC coating of claim 1, wherein the boiling points of the hydrocarbon monomer and the silane monomer are 100° C. or less at normal pressure.

3. 3. The DLC coating of claim 2, wherein the hydrocarbon monomer is methane, acetylene, benzene, or ethylene.

4. 3. The DLC coating of claim 2, wherein the silane monomer is silane, methylsilane, dimethylsilane, trimethylsilane, tetramethylsilane, ethylsilane, or diethylsilane.

5. 2. The DLC coating of claim 1, wherein the molar ratio of the hydrocarbon monomer to the silane monomer is from 60:40 to 95:

5.

6. 2. The DLC coating of claim 1, wherein the DLC coating has a thickness of 5-100 nm.

7. A manufacturing apparatus for DLC coating according to any one of claims 1 to 6, a plasma reactor used to deposit the DLC coating by PECVD; A monomer gasification control device used to heat and gasify a hydrocarbon monomer that is liquid at room temperature or to control the state of gasification of a silane monomer; a gas flow meter used to measure the flow rate of the monomer whose gasification is controlled; and a heat retention device used to keep a monomer flow path warm so as to ensure stable introduction of gasified monomer in the monomer gasification control device to the plasma reactor.

8. 8. The DLC coating manufacturing apparatus according to claim 7, further comprising a pressure gauge provided between the monomer gasification control device and the gas flow meter, and controlling the temperature of the monomer gasification control device based on a value read from the pressure gauge.

9. A method for producing a DLC coating according to any one of claims 1 to 6, comprising the steps of: providing a substrate and placing the substrate in a plasma reactor; and metering the hydrocarbon monomer and silane monomer gases into the plasma reactor and turning on a bias power supply to deposit a DLC coating on the substrate by a PECVD process.

10. The method for producing a DLC coating according to claim 9, wherein the hydrocarbon monomer and the silane monomer are introduced as gases and are measured by gas flow meters.

11. The method for producing a DLC coating according to claim 10, wherein the pressure of the silane monomer gas is controlled to be 0.001 MPa to 0.003 MPa by controlling the temperature of the silane monomer.

12. The method for producing a DLC coating according to claim 10, wherein the flow rate of the hydrocarbon monomer is 10-200 sccm, and the flow rate of the silane monomer is 5-100 sccm.

13. The method for producing a DLC coating according to claim 10, characterized in that an inert gas is introduced at a flow rate of 20 to 200 sccm while the monomer gas is being introduced.

14. The method for producing DLC ​​coating according to claim 10, characterized in that the pressure in the plasma reactor is 15-100 mT, the bias voltage input is -200--800 V, and the deposition time of the coating is 2-30 min.

15. A composite coating, comprising the DLC coating according to any one of claims 1 to 6 and an AF coating formed on the DLC coating.

16. The composite coating of claim 15, wherein the AF coating raw material comprises a perfluoropolyether polymer.

17. 17. The composite coating of claim 16, wherein the perfluoropolyether polymer is a perfluoropolyether silane or a perfluoropolyether alkoxy silane.

18. The composite coating of claim 15, wherein the AF coating has a thickness of 5-20 nm.

19. The composite coating of claim 15, wherein the AF coating is deposited by vacuum deposition.

20. An application product, characterized in that at least a part of the surface thereof is provided with a composite coating according to any one of claims 15 to 19.

21. The application product according to claim 20, which is a touch panel.

22. The coated product according to claim 20, wherein the color difference value before and after coating is 0.5 or less.

23. The coating product according to claim 20, characterized in that the substrate of the coating surface of the product is glass, and according to the steel wool test, after 6000 reciprocations under a load of 10 N, the speed is 40 cycles / min, the test direction is the same as the fiber direction of the steel wool, the test stroke is 40 mm, and the contact angle is observed to be 100° or more.

24. The coating product according to claim 20, characterized in that the substrate of the coating surface of the product is plastic, and according to the steel wool test, after 800 reciprocations under a load of 1N, the speed is 40 cycles / min, the test direction is the same as the fiber direction of the steel wool, the test stroke is 40 mm, and the contact angle is observed to be 100° or more.

Citation Information

Patent Citations

  • Liquid raw material evaporating device

    JP1989083663A

  • Film deposition apparatus, film deposition method, and film deposition program

    JP2014189898A

  • Stain-proof article

    JP2018094918A

  • Fluorocarbon film and method for forming same

    WO2006008841A1